Combustion characteristics and arsenic retention during co-combustion of agricultural biomass and bituminous coal. (August 2016) - Zhou, Chuncai; Liu, Guijian; Wang, Xudong; Qi, Cuicui; Hu, Yunhu
Highlights: The thermochemical behavior of bituminous and biomass were evaluated. The kinetic properties of their blends were obtained. The arsenic retention behavior during co-combustion were studied. Abstract: A combination of thermogravimetric analysis (TG) and laboratory-scale circulated fluidized bed combustion experiment was conducted to investigate the thermochemical, kinetic and arsenic retention behavior during co-combustion bituminous coal with typical agricultural biomass. Results shown that ignition performance and thermal reactivity of coal could be enhanced by adding biomass in suitable proportion. Arsenic was enriched in fly ash and associated with fine particles during combustion of coal/biomass blends. The emission of arsenic decreased with increasing proportion of biomass in blends. The retention of arsenic may be attributed to the interaction between arsenic and fly ash components. The positive correlation between calcium content and arsenic concentration in ash suggesting that the arsenic–calcium interaction may be regarded as the primary mechanism for arsenic retention.